2021
DOI: 10.3390/ijerph18147648
|View full text |Cite
|
Sign up to set email alerts
|

How Artificial Intelligence and New Technologies Can Help the Management of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has worked as a catalyst, pushing governments, private companies, and healthcare facilities to design, develop, and adopt innovative solutions to control it, as is often the case when people are driven by necessity. After 18 months since the first case, it is time to think about the pros and cons of such technologies, including artificial intelligence—which is probably the most complex and misunderstood by non-specialists—in order to get the most out of them, and to suggest future improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The COVID-19 pandemic has also highlighted the broad-spectrum potential of AI . In a recent review [ 26 ], for example, relevant papers were selected that address the adoption of artificial intelligence and new technologies in the management of pandemics and communicable diseases such as SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic has also highlighted the broad-spectrum potential of AI . In a recent review [ 26 ], for example, relevant papers were selected that address the adoption of artificial intelligence and new technologies in the management of pandemics and communicable diseases such as SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…The three illustrated potentials [ 25 , 26 , 27 ] are also important in DP. In fact, in DP, the need for categorizing images merges with the need to make decisions and/or deduce approaches through actions on large databases and data sets or with other needs not based on medical images [ 1 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that AI can help interpret CXRs effectively in COVID-19 patients [16]. Khuzani et al showed that a CXR AI classifier trained on 420 images can accurately classify, with 94% accuracy, the CXR images into normal, COVID-19 and non-COVID-19 pneumonia, based on imaging findings alone [17]. Naturally, combining different modes of data used in clinical medicine to predict the events in COVID-19 patients has become the goal of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two years, new technologies such as AI proved helpful in the management of the COVID-19 pandemic [12][13][14][15][16][17][18]. During the first months of 2020, chest computedtomography scans showed the extent of lung damage caused by COVID-19; accordingly, efforts were established around the world to facilitate data sharing, model training, and scan assessment [10,15].…”
mentioning
confidence: 99%